Advances in Visual Computing 6th International Symposium, ISVC 2010, Las Vegas, NV, USA, November 29 - December 1, 2010, Proceedings, Part III - Bebis, George; Boyle, Richard; Parvin, Bahram; Koracin, Darko; Chung, Ronald; Hammound, Riad.; Hussain, Muhammad; Kar-Han, Tan.; Crawfis, Roger; Thalmann, Daniel; Kao, David; Avila, Lisa.; et al. (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
It is with great pleasure that we present the proceedings of the 6th Inter- tional, Symposium on Visual Computing (ISVC 2010), which was held in Las Vegas, Nevada. ISVC provides a common umbrella for the four main areas of visual computing including vision, graphics, visualization, and virtual reality. The goal is to provide a forum for researchers, scientists, engineers, and pr- titioners throughout the world to present their latest research ?ndings, ideas, developments, and applications in the broader area of visual computing. This year, the program consisted of 14 oral sessions, one poster session, 7 special tracks, and 6 keynote presentations. The response to the call for papers was very good; we received over 300 submissions for the main symposium from which we accepted 93 papers for oral presentation and 73 papers for poster p- sentation. Special track papers were solicited separately through the Organizing and Program Committees of each track. A total of 44 papers were accepted for oral presentation and 6 papers for poster presentation in the special tracks.
Poster Session -- Lunar Image Classification for Terrain Detection -- Surface Modeling of the Corpus Callosum from MRI Scans -- Track Detection for Autonomous Trains -- Local Descriptors for Document Layout Analysis -- CT Image Segmentation Using Structural Analysis -- Phase Space for Face Pose Estimation -- Contour Based Shape Retrieval -- Illumination Normalization for Robust Face Recognition Using Discrete Wavelet Transform -- Feature-Based Lung Nodule Classification -- Multiple-object Tracking in Cluttered and Crowded Public Spaces -- Compliant Interframe Coding for Motion-JPEG2000 -- EVP-Based Multiple-View Triangulation -- An Improved Shape Matching Algorithm for Deformable Objects Using a Global Image Feature -- Multi-scale Topo-morphometric Opening of Arteries and Veins: An Evaluative Study via Pulmonary CT Imaging -- Video Event Detection as Matching of Spatiotemporal Projection -- PixelLaser: Computing Range from Monocular Texture -- A Spatio-Spectral Algorithm for Robust and Scalable Object Tracking in Videos -- Driving Fatigue Detection Using Active Shape Models -- Outlier Removal in Stereo Reconstruction of Orbital Images -- Random Sampling Nonlinear Optimization for Camera Self-calibration with Modeling of Intrinsic Parameter Space -- Facial Fraud Discrimination Using Detection and Classification -- Segmentation of Abdominal Organs Incorporating Prior Knowledge in Small Animal CT -- Method of Interest Points Characterization Based C-HOG Local Descriptor -- Stereo-Based Object Segmentation Combining Spatio-Temporal Information -- Fast Motion Estimation Based on Search Range Adjustment Using Neighboring MVDs -- Towards Computational Understanding of Skill Levels in Simulation-Based Surgical Training via Automatic Video Analysis -- Biomedical Image Retrieval in a Fuzzy Feature Space with Affine Region Detection and Vector Quantization of a Scale-Invariant Descriptor -- Model Distribution Dependant Complexity Estimation on Textures -- Integrating Multiple Uncalibrated Views for Human 3D Pose Estimation -- A Novel Histogram-Based Feature Representation and Its Application in Sport Players Classification -- Facial Expression Recognition Using Facial Features and Manifold Learning -- Blurring Mean-Shift with a Restricted Data-Set Modification for Applications in Image Processing -- Detecting Straight Line Segments Using a Triangular Neighborhood -- Size Distribution Estimation of Stone Fragments via Digital Image Processing -- Image Enhancement by Median Filters in Algebraic Reconstruction Methods: An Experimental Study -- 3D Curvature-Based Shape Descriptors for Face Segmentation: An Anatomical-Based Analysis -- Computational Hemodynamics in Intracranial Vessels Reconstructed from Biplane Angiograms -- Object Distance Estimation Based on Stereo Vision and Color Segmentation with Region Matching -- Multiscale Information Fusion by Graph Cut through Convex Optimization -- A Fast Level Set-Like Algorithm for Region-Based Active Contours -- A Novel Hardware Architecture for Rapid Object Detection Based on Adaboost Algorithm -- Using Perceptual Color Contrast for Color Image Processing -- GPU Acceleration of Robust Point Matching -- A Wavelet-Based Face Recognition System Using Partial Information -- A Study of Hierarchical Correlation Clustering for Scientific Volume Data -- Subversion Statistics Sifter -- A Lossy/Lossless Coding Algorithm Using Histogram -- Stereo Matching in Mean Shift Attractor Space -- Undecimated Wavelet Transform-Based Image Interpolation -- The Influence of Multimodal 3D Visualizations on Learning Acquisition -- Visualizing Gene Co-expression as Google Maps -- A New Approach for Lighting Effect Rendering -- SemaTime - Timeline Visualization of Time-Dependent Relations and Semantics -- Comics Stylizations of 3D Scenes Using GPU -- Discovering Novelty in Gene Data: From Sequential Patterns to Visualization -- A Differential-Geometrical Framework for Color Image Quality Measures -- Three Dimensional Reconstruction Using Vertical Constraints from a Photograph -- A Framework for Visual and Haptic Collaboration in Shared Virtual Spaces -- Design and Costs Estimation of Electrical Substations Based on Three-Dimensional Building Blocks -- Generating Shaded Image with Lighting Using Image Fusion Space -- Automatic Detection of Morphologically Distinct Objects in Biomedical Images Using Second Generation Wavelets and Multiple Marked Point Process -- Imaging-Based Computation of the Dynamics of Pelvic Floor Deformation and Strain Visualization Analysis -- Exploiting Multiple Cameras for Environmental Pathlets -- On Supervised Human Activity Analysis for Structured Environments -- Human Behavior Analysis at a Point of Sale.
Keywords: Computer science; User interfaces (Computer systems).; Computer graphics; Image processing; Pattern recognition; Bioinformatics; Computer Science; Pattern Recognition; Computational Biology/Bioinformatics.; Computer Graphics; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction; Electronic books